A two-echelon location-routing problem for biomass logistics systems. (February 2021) - Cao, Jin Xin; Wang, Xiangting; Gao, Jiachen
Abstract : Biomass has attracted considerable attention from both researchers and practitioners as an important renewable energy source that can help achieve sustainable development. However, inefficient biomass logistics systems hinder the development of biomass utilisation. This study investigates a two-echelon biomass resource location-routing problem (2E-BRLRP). Considering a predetermined supply of biomass resources, a mixed integer programming model for the 2E- BRLRP is established to determine the best locations for biomass collection facilities and corresponding vehicle routes. To address the computational complexity, a hybrid heuristic algorithm that embeds variable neighbourhood search into the tabu search framework is developed. A set of comprehensive computational examples are used to test the effectiveness and efficiency of the proposed approach. Highlights: This study investigates a two-echelon biomass resource location-routing problem. A novel mixed integer programming model is established for the proposed problem. A hybrid heuristic algorithm is developed for problem solution. Comprehensive computational examples are conducted to verify the proposed approach.